Effect of Some Bio Variables on Gestational Diabetes Progression: (Review) - Alzahraa Ibrahim Abdul Majeed; Ekhlas Abdallah Hassan; Wijdan Amer Ibrahim; Wafaa Sh. Al – Zuhairi (ASJ - Academic Science Journal, 2023)
Gestational diabetes mellitus (GDM) is the most common metabolic disorder and is also definedas: impairment of glucose tolerance. This article aims to clarify the role of the changes in somehormones that may cause the development gestational of diabetes, as an attempt to understandand reduce the mechanism of this disorder. Disturbance Hormonal insulin levels, which arecharacterized by a reducing blood glucose reduced utilization of by muscle and body tissues.Many factors will promote the development of GDM, such as: BMI ≥ 30 Kg/m2, pre-existinggestational diabetes, family history and HbA1C ≤ 7 mmol/l. Gestational diabetes can be seenas a transient pattern of type 2 Diabetes, Symptoms appear with hormonal changes related topregnancy. Etiology of GDM related to type 2 diabetes and insulin resistant which also mayattack beta cells in pancreas. It can be concluded that the change in the level of each of thesehormones (significant differences) had a role in promoting the development of diabeticpregnant more than control pregnant women.